2008
DOI: 10.1101/gad.1708608
|View full text |Cite
|
Sign up to set email alerts
|

RMI, a new OB-fold complex essential for Bloom syndrome protein to maintain genome stability

Abstract: [Keywords: Bloom syndrome; BLM; BLAP75; RMI1; RMI2; Topoisomerase 3␣] Supplemental material is available at http://www.genesdev.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

20
284
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 186 publications
(304 citation statements)
references
References 43 publications
(65 reference statements)
20
284
0
Order By: Relevance
“…1D). Top3α and RMI1 coimmunoprecipitated with both Flag-tagged RMI2 proteins as has been observed previously (7,12). These data indicate that the Lys121Ala sequence change in RMI2 specifically abrogates binding to FANCM and identify a role for RMI2 in FANCM binding.…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…1D). Top3α and RMI1 coimmunoprecipitated with both Flag-tagged RMI2 proteins as has been observed previously (7,12). These data indicate that the Lys121Ala sequence change in RMI2 specifically abrogates binding to FANCM and identify a role for RMI2 in FANCM binding.…”
Section: Resultssupporting
confidence: 84%
“…Previous studies have shown that the C-terminal OB domain of RMI1 (RMI1 OB2) interacts both with the MM2 region of FANCM and with RMI2 ( Fig. 1A) (7,8,12,13,17). We have confirmed the RMI/FANCM interaction in vitro by demonstrating that a glutathione S-transferase (GST)-MM2 fusion protein forms a complex with the RMI core complex (RMI1 OB2 in complex with RMI2) using analytical size-exclusion chromatography (Fig.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations